2007
DOI: 10.1016/j.neuroscience.2007.02.025
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar cortical-layer-specific control of neuronal migration by pituitary adenylate cyclase-activating polypeptide

Abstract: Migration of immature neurons is essential for forming the cortical layers and nuclei. Impairment of migration results in aberrant neuronal cytoarchitecture, which leads to various neurological disorders. Neurons alter the mode, tempo and rate of migration when they translocate through different cortical layers, but little is known about the mechanisms underlying this process. Here we show that endogenous pituitary adenylate cyclase-activating polypeptide (PACAP) has short-term and cortical-layer-specific effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
86
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(89 citation statements)
references
References 98 publications
(188 reference statements)
2
86
1
Order By: Relevance
“…1H. In contrast to our results, previous reports showed that PACAP inhibits the migration of immature granule neurons in the Purkinje cell layer at the postnatal stage (43,44). On the other hand, it has been reported that a high concentration of PACAP induces G q signaling (45), and G q signaling induced by the endothelin receptor inhibits the migration of NPCs (9).…”
Section: Discussioncontrasting
confidence: 99%
“…1H. In contrast to our results, previous reports showed that PACAP inhibits the migration of immature granule neurons in the Purkinje cell layer at the postnatal stage (43,44). On the other hand, it has been reported that a high concentration of PACAP induces G q signaling (45), and G q signaling induced by the endothelin receptor inhibits the migration of NPCs (9).…”
Section: Discussioncontrasting
confidence: 99%
“…For example, isolated granule cells in cerebellar microexplant cultures slow, eventually becoming stationary in culture over a time course that is similar to their in vivo development (Yacubova and Komuro, 2002; see also Trenkner et al, 1984). Alternatively, extrinsic factors may have a vital role, as several secreted molecules have been shown to suppress or promote neuron motility (Powell et al, 2001;Polleux et al, 2002;Pozas and Ibáñez, 2005;Cameron et al, 2007;Lysko et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…It became apparent that granule cell migration is controlled by the orchestrated activity of multiple molecular events at the right time and right place, including pathway selection, activation of specific receptors and channels, and assembly and disassembly of cytoskeletal components (18)(19)(20)(21)(22). However, the question of how natural environmental stimuli are involved in controlling granule cell migration has been poorly understood.…”
mentioning
confidence: 99%